2017
DOI: 10.1039/c7ra01077j
|View full text |Cite
|
Sign up to set email alerts
|

A wheat straw cellulose based semi-IPN hydrogel reactor for metal nanoparticles preparation and catalytic reduction of 4-nitrophenol

Abstract: A wheat straw cellulose-g-poly(acrylic acid)/poly(vinyl alcohol) semi-IPN hydrogel (WSC-g-PAA/PVA) was synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…48 However, 4-AP containing a -NH 2 group is widely used in a lot of industries, including pharmaceuticals and dye intermediates. [49][50][51] The process of the catalytic reduction of 4-NP to 4-AP can be detected using the UV-vis absorption spectroscopy because a continuous decrease in the absorption peak at 401 nm can be observed during the reaction. As shown in Fig.…”
Section: Preparation and Catalytic Performance Of The Aunp/t-g Hydrogelmentioning
confidence: 99%
“…48 However, 4-AP containing a -NH 2 group is widely used in a lot of industries, including pharmaceuticals and dye intermediates. [49][50][51] The process of the catalytic reduction of 4-NP to 4-AP can be detected using the UV-vis absorption spectroscopy because a continuous decrease in the absorption peak at 401 nm can be observed during the reaction. As shown in Fig.…”
Section: Preparation and Catalytic Performance Of The Aunp/t-g Hydrogelmentioning
confidence: 99%
“…reported that the triazolylbiferrocene‐containing polymers synthesized by using the ring‐opening metathesis polymerization (ROMP) could react with HAuCl 4 to produce mixed‐valent triazolylbiferrocenium polyelectrolyte networks that encapsulate AuNPs . Furthermore, for the efficient use of AuNPs as catalysts, it is necessary to immobilize AuNPs in certain supports, not only to inhibit the aggregation of AuNPs caused by their high surface energy but also to make the catalysts recyclable for repeated use . Therefore, various carriers have been proposed to immobilize and disperse AuNPs, including fibers and hydrogels .…”
Section: Introductionmentioning
confidence: 99%
“…1 Nitrophenol and its derivatives are organic pollutants which are mostly used in agricultural, textile, paper, explosives and pharmaceutical industries. 2,3 They are potentially hazardous and mutagenic to humans and the general ecosystem. 2,4 Among the derivatives of nitrophenols, 4-nitrophenol is found to be highly toxic, stable and biorefactory in nature.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 They are potentially hazardous and mutagenic to humans and the general ecosystem. 2,4 Among the derivatives of nitrophenols, 4-nitrophenol is found to be highly toxic, stable and biorefactory in nature. 2,4 Therefore, the removal of 4-nitrophenol from industrial wastewaters is essential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation